2011
DOI: 10.1007/s11144-011-0300-9
|View full text |Cite
|
Sign up to set email alerts
|

Water–gas shift activity of K-promoted (Ni)Mo/γ-Al2O3 systems in sulfur-containing feed

Abstract: The effect of potassium additive on the catalytic activity of nickelmolybdenum alumina-supported systems has been studied by varying the molybdenum content within 5-18 mass% MoO 3 , reaction temperature from 180 to 400 (500)°C, and steam to gas ratio of 0.3, 0.7, and 1. It has been established that potassium reduces the activity of one-component Mo-containing samples, while, independent of molybdenum loading, nickel promotes activity within the whole temperature range studied and extends the temperature range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The S/Mo ratios in supported Mo–S catalysts trended in the following order: Mo–S/ZrO 2 (0.84) > Mo–S/Al 2 O 3 (0.67) > Mo–S/TiO 2 (0.43) > Mo–S/SiO 2 (0.24) > Mo–S/CeO 2 (0.16). This result agreed with the trend of MoO 3 reducibility and correlated with the CO consumption rate observed after 72 h of WGS reaction (Figure ) and strongly suggested that the Mo–S species are responsible for the WGS activity of supported Mo–S catalysts. …”
Section: Results and Discussionsupporting
confidence: 87%
“…The S/Mo ratios in supported Mo–S catalysts trended in the following order: Mo–S/ZrO 2 (0.84) > Mo–S/Al 2 O 3 (0.67) > Mo–S/TiO 2 (0.43) > Mo–S/SiO 2 (0.24) > Mo–S/CeO 2 (0.16). This result agreed with the trend of MoO 3 reducibility and correlated with the CO consumption rate observed after 72 h of WGS reaction (Figure ) and strongly suggested that the Mo–S species are responsible for the WGS activity of supported Mo–S catalysts. …”
Section: Results and Discussionsupporting
confidence: 87%
“…18 A NiMo-based catalyst for the WGS reaction is also investigated with less publication. [19][20][21] One of the interesting recent catalyst developments in sulfur tolerant catalysts is the use of lanthanide oxysulphides (La 2 O 2 S or Pr 2 O 2 S) for high temperature WGS and RWGS reactions at high concentration of sulfur. The unique properties of this catalyst are that even though it has no transition metal which is commonly used in WGS catalysts, it has a very large oxygen storage capacity which makes it able to perform WGS at an ultra-high temperature (>600 °C) in the presence of high concentration of sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Re is a good choice to replace the Pt group metal catalyst due to its excellent electrochemical properties, lower cost compared to Pt metal and sustainable sources. Recently, water-gas shift activity in Re-based catalysts was studied, and the results showed that Re supported on an alumina catalyst promoted by K and Co exhibited an excellent performance for the WGS reaction [12]. In addition, the water-gas shift activity of Pt-Re bimetallic and Pt alone supported on a zirconia-doped ceria has been evaluated [13].…”
Section: Introductionmentioning
confidence: 99%